A method for treating oil palm biomass - Hassan, Mohd Ali; Samsu Baharuddin, Azhari; Lim, Siong Hock; Sulaiman, Alawi; Mohd Yusoff, Mohd Zulkhairi; Kamal Bharin, Ezyana; Mokhtar, Mohd Noriznan; Nishida, Haruo; Shirai, Yoshihito; Wakisaka, Minato (2011)
The present invention relates to a method for treating oil palm biomass using high pressure steam and/or superheated steam available at the palm oil mill which is operated at temperature range 100?C-350?C and pressure range 40-450psig (0.27-3.1MPa) for up to 180 minutes of holding time to enhance its degradation characteristics for potential use as a feedstock material for production of high value-added bioproducts such as biocompost, biogas, biohydrogen, biosugar, bioethanol and others. The oil palm biomass is such as empty fruit bunches, frond, mesocarp fibres, palm oil mill effluent (POME) solid and anaerobic sludge or any combination thereof.